The Influence of Understanding The Code of Ethics of The Accountant Profession and Student Intelligence on the Ethical Behavior of Accounting Students - Rosdiana, Mega; Sumanto, Agus; Wuryaningrum, Rica (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study examines the influence of understanding the code of ethics in the accounting profession and student intelligence on the ethical behavior of accounting students. Ethical behavior in the professional and academic context has become a critical issue due to increasing cases of financial irregularities. Students, especially those studying accounting, play a crucial role in maintaining ethical standards in financial reporting and broader economic activities. The research seeks to understand how students' knowledge of ethical guidelines in accounting, combined with their cognitive abilities, influences their ethical conduct. The results suggest that both a strong understanding of professional ethics and high intelligence contribute positively to fostering ethical behavior among accounting students. This finding is essential in designing educational programs that integrate both ethical teachings and intellectual development to prepare future accountants for the challenges of their profession.